Managerial Ownership Influencing Tunnelling Behaviour - Agung Juliarto; Greg Tower; Mitchell Van der Zahn; Rusmin Rusmin (Australasian Accounting, Business and Finance Journal, 2013)
This study investigates the extent and the determinants of tunnelling behaviour in five ASEAN countries (i.e. Indonesia, Malaysia, Philippines, Singapore, and Thailand). Related party transactions (RPTs) in the form of loans to related parties are used as the proxy for tunnelling. With 200 firm-year observations over the period 2006-2009, this study finds a positive association between managerial ownership and the extent of tunnelling. The other important findings are that business environment (BE), foreign ownership, and independent directors are ineffective governance mechanisms to rein in tunnelling behaviour. This suggests that regulators need to evolve more effective governance mechanisms.
Keywords: Tunnelling; Tunneling; related party transactions; business environment; ownership; ASEAN